Malay mathematical game for primary students - Chong, Hui Hui (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Games can be a very productive way of reaching students who cannot respond top conventional teaching method. Learning activities can be successful through playing game. Mathematics is a challenging subject for all ranges of people, especially for the primary student who are the new to learn the mathematics skills. They have to deep understanding of basic mathematics skills to solve the problem-solving questions. They need to have a very strong basic mathematics skill in order to go to the next level of mathematics skill. In this project, a Malay mathematical game is proposed for the Malay-educated primary students in order to attract the primary students to get interested in learning mathematics. This application can contribute benefit for students to train their mathematics skills. An attractive interface is designed to make the application more attractive and interesting. There are different types of gameplay to let the users decide whether they can play alone or play among their friends. In order to fulfil the user requirements for this application, testing and evaluation are done with the 15 primary students and three teachers from Sekolah Kebangsaan Paya Mebi. Based on the testing and evaluation result, the majority of the users satisfied with the interface design and the functionality of the Malay mathematical game.